Comparative Study of Physicochemical properties of Soil, Aheri, Maharashtra & Effect of Vermicompost Fertilizer (Indian Journal of Agriculture Engineering (IJAE), 2024)
Farmers are using chemical fertilizer for farming to extend the yield of crops. Chemical fertilizer reduces soils fertility and it also contaminate ground water table..Recycling of biowaste is necessary to reduces waste .It makes our campus clean likewise as contribute in sustainable development. This waste are often converted into useful fertilizer as a Vermicompost.Vermicompost will enrich the soil and its fertility. Vermicompost also results in decrease the environmental problems. Vermicompost could be a vital biofertilizer and Vermicompost is enriched with all beneficial soil bacteria and also contains many of the essential plant nutrients like N, P, K and micronutrients.(1) Vermicomposting is that the process of production of compost by breeding earthworms, leading to homogeneous and stabilized humus used as manure and significantly increased the quantity of N, P, K and C concentration in vermicompost. The aim of this paper to recycle biowaste and study various physicochemical property of soil and impact of vermicompost fertilizer on soils property of Aheri, Nagpur. The observed values of various physicochemical parameter in all soil samples, after addition of vemicompost is fairly good.